Synergistic flame retardant effect between nano-silicon dioxide and layered double hydroxides in ethylene vinyl acetate composites. (October 2018) - Qian, Yi; Zhou, Shaojie; Chen, Xilei
Layered double hydroxides (LDHs) were synthesized by a coprecipitation method. The synergistic flame retardant effect of nano-silicon dioxide (nano-SiO2 ) on ethylene vinyl acetate (EVA)/LDHs composites was studied using limiting oxygen index (LOI), cone calorimeter test (CCT), scanning electron microscopy (SEM), and thermogravimetric analysis (TGA). Results showed that the LOI values of the EVA/LDHs/nano-SiO2 composites were basically higher than that of the EVA/LDHs composite, and the EVA composite with 48% LDHs and 2% nano-SiO2 reached an LOI value of up to 31.2%. The CCT results indicate that the addition of nano-SiO2 greatly reduced the heat release rate, total heat release, mass loss, smoke production rate, total smoke release, and smoke factor. The morphology and structures of residues investigated by SEM gave positive evidence that char layers formed from the EVA/LDHs/nano-SiO2 composites were improved. The TGA data showed that the EVA/LDHs/nano-SiO2 composites show a higher thermal stability than the EVA/LDHs composites.